Natural products modulating MAPK for CRC treatment: a promising strategy - Zhou, Lin; Zhang, Jinlong; Zhao, Kangning; Chen, Bo; Sun, Zhen (Frontiers in Pharmacology, 2025)
Colorectal cancer (CRC) is a common malignant tumor of the digestive system, and the pathogenic mechanism is still unclear, mostly related to genetics, immunity, inflammation, and abnormal activation of tumor-related signaling pathways. MAPK belongs to the Ser/Thr kinase family, which plays an important role in complex cellular programs such as the regulation of cell proliferation, differentiation, apoptosis, angiogenesis, and tumor metastasis. Increasing evidence supports that MAPK activation is highly correlated with the risk of CRC. Targeting MAPK may be a therapeutic strategy, and natural products show great therapeutic potential in regulating MAPK-related proteins. In this paper, we searched PubMed, Web of Science and CNKI databases with keywords “colorectal cancer, natural products, MAPK pathway, ERK, P38, JNK” for relevant studies in the last 14 years from 2010 to 2024. This work retrieved 47 studies, aiming to provide new therapeutic strategies for CRC patients and lay the foundation for new drug development.